Manajemen Pembelajaran Untuk Mengembangkan Jiwa Kewirausahaan Pada Anak Usia Dini Di Tk Hang Tua Kota Bengkulu - Haryono, Mimpira; Suwarni, Suwarni; Bendriyanti, Rita Prima (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the application of project-based learning management in fostering an entrepreneurial spirit in early childhood at HANG TUA Kindergarten in Bengkulu City. The focus is on activities such as making crafts from recycled materials, a mini-market in the classroom, a buying and selling simulation, and providing simple services. Teachers act as facilitators, motivators, and directors, while parents and senior students act as partners providing guidance and support. The research method used a descriptive qualitative approach, collecting data through observation, interviews, teacher diaries, and documentation of children's activities. The results indicate that careful planning, participatory implementation, and systematic evaluation can enhance children's creativity, independence, social skills, critical thinking, communication, leadership, and understanding of simple economic values. In conclusion, project-based learning at HANG TUA Kindergarten effectively fosters entrepreneurial competencies, character, creativity, and social skills in early childhood, providing a fun learning experience that is relevant to real life and prepares children for future competency development.